Climate change in Asia and the Pacific how can countries adapt? - Anbumozhi, Venkatachalam; Breiling, Meinhard; Pathmarajah, Selvarajah; Reddy, Vangimalla R; Asian Development Bank Institute (Los Angeles, [California] London SAGE, 2012)
This volume examines the framework conditions for integrating climate change adaptation measures into agriculture, water, and natural resources management activities for the Asia and Pacific region. Based on the review of country experiences, the book describes key dimensions, suggests interventions for further exploration, and serves as a basis for planning and mainstreaming climate change adaptation into sectoral planning
At foot of title: ADBInstitute
Title from title screen (viewed October 20, 2023)
Includes bibliographical references and index
Description based on print version record
Keywords: Emergency management -- Asia; Emergency management -- Pacific Area; Climatic changes -- Environmental aspects -- Asia; Climatic changes -- Environmental aspects -- Pacific Area